Implementation and effect of concussion education in collegiate women`s ice hockey - Piana, L. E.; Garvey, K. D.; Kroshus, E.; Brook, E. M.; Matzkin, E. G. (The Physician and Sportsmedicine, 2020)
Objective: This study aimed to determine whether collegiate women`s ice hockey players are receiving pre-season concussion education and evaluate the nature and delivery of this education. Secondarily, we aimed to assess whether players who recall receiving this education have greater knowledge about concussion or are more likely to have reported suspected concussions than their peers.